Bronze age metalwork : techniques and traditions in the Nordic Bronze Age 1500-1100 BC - Wrobel Nørgaard, Heide (Archaeopress archaeology., 2018)
Bronze ornaments of the Nordic Bronze Age were elaborate objects that served as status symbols to communicate social hierarchy. An interdisciplinary investigation of the artefacts (dating from 1500-1100 BC) was adopted to elucidate their manufacture and origin, resulting in new insights into metal craft in northern Europe during the Bronze Age.